Completion Total Thyroidectomy in Occult Thyroid Cancer Patients after Partial Thyroidectomy - Syahrudi, Syahrudi; Wijayahadi, R Yoga (Folia Medica Indonesiana, 2021)
Thyroid cancer is one of the commonest cancer while the incidence of occult thyroid cancer is only 0,05%. Completion total thyroidectomy as one of the treatment choice for thyroid cancer which initially diagnosed preoperatively as benign thyroid mass, remains controversial. The aim of this study is to understand the effectiveness of completion total thyroidectomy after partial thyroidectomy, by analyzing from: proportion of malignant contralateral thyroid tissue, post operative complications, and recurrence of cancer. This retrospective study collected medical record datan between 2011 and 2016. Total sample were 16 patients (15 females, 1 male). There was no significant difference on contralateral thyroid tissue malignancy proportion between completion total thyroidectomy and without total thyroidectomy (p=0,375). It was found 3 surgical complications (50%) from 6 patients with completion total thyroidectomy and 3 complications (30%) from 10 patients without completion total thyroidectomy. The complications were temporary injury of recurrent laryngeal nerve (p=0,511), seroma (p=0,375), and hypoparathyroidism (p=0,375). No recurrence event after 4 years follow up amount both groups. In conclusion, there is no advantage in completion total thyroidectomy analized from proportion of malignant contralateral thyroid tissue, post operative complication and recurrence in 4 years-follow up.